The Implication of the Sima’an Ahad Pahing on the Qur'an Memorization at PPTQ Al-Hasan Ponorogo - Roni Susanto; Wahyu Widodo; Nur Kolis (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2023)
The digital era leaves problems of credibility and authenticity for those who memorize the Qur'an. The question of credibility could be seen by the decrease in the quality of reading, such as makharij and tajwid. In contrast, the question of authentication is evidenced by the low quality of students' memorization. This study aims to discuss the implications of the Sima’an Ahad Pahing activity on students’ memorization at PPTQ Al-Hasan Ponorogo. This study departs from cognitive, affective, and psychomotoric problems with the reinforcement of the psychological theory of behaviorism developed by John Watson. This study uses a qualitative method with a psychological approach. Data sources were obtained through interviews with 1 kiai, 4 ustadz, and 5 students. The analysis used in this study is Huberman & Saldana, which includes three steps, namely data compaction, data presentation, and drawing conclusions. The results showed that implicitly the Sima’an at PPTQ Al-Hasan Ponorogo provided a new method for maintaining the credibility and authenticity of the students' memorization.